Occupational Sitting Posture and Lower Back Pain Among Employees: A Cross-Sectional Study - Simarmata, Vidi Posdo A.; Novelyn, Silphia; Situmorang, Daniel R. Parsaoran (Journal of Public Health Sciences, 2025)
Low back pain refers to discomfort in the lower back that can interfere with daily tasks. Health centers are work environments that involve ergonomic activities such as lifting, pushing, pulling, reaching, carrying objects, and handling patients, all of which present potential hazards that may lead to musculoskeletal disorders. This study investigates whether low back pain among employees at the Merdeka Health Center in 2024 is associated with their sitting posture while working. The research applied an analytical survey with a cross-sectional design, using a questionnaire to collect primary data from 35 respondents who met the inclusion criteria. The majority of respondents were female (82.9 percent), aged between 26 and 35 years (40 percent), and worked in functional positions (51.4 percent). Most reported using chairs with backrests while working (82.9 percent), not sitting with a hunched posture (60 percent), and working less than six hours per day (62.9 percent). Statistical analysis produced a p-value of 0.564, indicating no significant association between sitting posture and the occurrence of low back pain. Based on the findings from both the past week and past year, there is no meaningful relationship between sitting position at work and low back pain among employees of the Merdeka Health Center in Bogor City.